Cyber Security of Market-Based Congestion Management Methods in Power Distribution Systems - Mohammed, Omniyah Gul (2021)
As the penetration rate of flexible loads and Distributed Energy Resources in the distribution networks increases, congestion management techniques that utilize Demand Side Management (DSM) have been developed. These are indirect methods that rely on information exchange between the Distribution Network Operator, aggregators, and consumers’ meters to encourage customers to change their demand to relieve congestion. Cyber attacks against aggregators can compromise the operation of DSM-based congestion management methods, and hence, affect the security and reliability of electrical networks. In this paper, the vulnerability of indirect congestion management methods to Load Altering Attacks is studied. An optimizationalgorithm is developed to determine the aggregators a cyber attacker would compromise, via minimum alteration of their load profiles, to cause congestion problems. The impact of such attacks on congestion and consumers’ electricity bill is then studied. A mitigation scheme is formulated to determine the most critical aggregators in the network. The security of these aggregators is then reinforced to mitigate such cyber attacks.